Deep-Water Seafloor Undulations Related to Bottom Currents: A Case Study from the Shenhu Canyon Area, Northern South China Sea - Junjun Zhang; Xishuang Li; Xiaoqing Xu; Lejun Liu; Qingjie Zhou (Journal of Marine Science and Engineering, 2026)
Bottom currents and their associated sedimentary structures are key agents in shaping deep-sea morphodynamics, among which the genesis of seafloor undulations is still debated, restricting engineering risk assessment and resource development safety. Based on high-resolution multibeam bathymetry, sub-bottom profiles, and near-bottom current observations, this study analyzes morphological characteristics, internal reflection structures, and near-bottom current dynamic processes of seafloor undulations in the Shenhu canyon area. The results indicate that undulations occur at canyon heads, canyon interfluve, and east side of canyon. The undulations are generally characterized by vertical aggradation, with some sediment waves exhibiting directional crestline migration accompanied by wave merging, indicating the existence of persistent sediment transport processes. Within the canyon, the flow is concentrated and exhibits significant vertical deflection, reflecting the pronounced flow-guiding effect of the confined topography on near-bottom currents, which consequently controls the lateral migration of crestlines on both sides of the canyon and the shaping of seafloor undulations at canyon heads by internal tides. In contrast, in the relatively open canyon interfluve, flow directions are more dispersed, predominantly characterized by weaker currents. These findings contribute to the understanding of deep-water sedimentary dynamic processes and provide a reference for interpreting the genesis of similar deep-water seafloor undulations.